2006
DOI: 10.1007/s10517-006-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dipeptide N-acetylaspartylglutamate on denervation-induced changes in the volume of rat skeletal muscle fibers

Abstract: N-acetylaspartylglutamate prevents the denervation-induced increase in the volume of muscle fibers in rat diaphragm, the phenomenon being more pronounced for the hydrolysable isomer. The effect of dipeptide manifested against the background of blockade of metabotropic glutamate receptors. It was hypothesized that N-acetylaspartylglutamate is involved in the regulation of the volume of skeletal muscle fibers via activation of ionotropic receptors by both dipeptide and glutamate molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Nerve transection significantly increases muscle fiber cross-section, but as shown in the rat phrenic muscle, ethylglutamic acid, an mGlu2/3 receptor antagonist had no effect on denervation-induced increase in muscle fiber volume. This indicates that mGlu2/3 may not be involved in the effect of N-acetylaspartylglutamate in the volume of skeletal muscle fiber after denervation (Malomuzh et al, 2006).…”
Section: Metabotropic Glutamate Receptors In the Muscloskeletal Smentioning
confidence: 92%
“…Nerve transection significantly increases muscle fiber cross-section, but as shown in the rat phrenic muscle, ethylglutamic acid, an mGlu2/3 receptor antagonist had no effect on denervation-induced increase in muscle fiber volume. This indicates that mGlu2/3 may not be involved in the effect of N-acetylaspartylglutamate in the volume of skeletal muscle fiber after denervation (Malomuzh et al, 2006).…”
Section: Metabotropic Glutamate Receptors In the Muscloskeletal Smentioning
confidence: 92%
“…In short, the metabonomic analysis results of this study strongly suggest that the accumulation of these important metabolites of glutamate, n-acetyl-1-aspartylglutamic acid, l-2-aminoadipic acid, 3-hydroxybutyric acid, and bilirubin may directly contribute to promoting the development of embryonic duck skeletal muscle. Glutamate plays a key role in all transamination reactions in the body and in many other metabolic pathways in different organs (including skeletal muscle) [ 26 ], and n-acetyl-1-aspartylglutamic acid also affects muscle development [ 27 ]. Sato et al showed that l-2-aminoadipic acid regulates protein turnover of C2C12 myotube [ 28 ], and 3-hydroxybutyric acid possesses a key role in promoting muscle development and maintaining muscle protein balance [ 29 ].…”
Section: Discussionmentioning
confidence: 99%